Ab initio MCDHF/RCI and semi-empirical HFR calculations of transition probabilities and oscillator strengths in Xe XI. (September 2019) - Bokamba Motoumba, E.; Enzonga Yoca, S.; Quinet, P.; Palmeri, P.
Highlights: A theoretical investigation of the atomic structure of Xe XI is presented using two independent methods, i.e. the ab initio MCDHF/RCI and semi-empirical HFR approaches. A set of radiative parameters for 576 electric dipole transitions of Xe XI falling in the EUV spectral range 102 Å–157 Å is reported. It is found that the inclusion of interacting configurations with more than one hole in the 4p core subshell decrease systematically the transition rates by 20%. Abstract: The atomic structure of ten-times ionized xenon (Xe XI) has been computed by two independent methods, i.e. the ab initio relativistic multiconfiguration Dirac–Hartree–Fock (MCDHF) approach within the relativistic configuration interaction (RCI) approximation and the semi-empirical pseudo-relativistic Hartree–Fock (HFR) method. The transition probabilities and oscillator strengths of the 4d 8 − (4p 5 4d 9  + 4d 7 5p + 4d 7 4f) transition array have been determined in both models and allowed us to estimate their accuracy taking into account both the gauge agreements and the cancellation effects on the line strengths. It has been found that core – core and core – valence correlations through the explicit inclusion of single- to triple-hole 4p-subshell configurations in our RCI model systematically decrease the transition rates by about 20% for the strong lines (with log gf > 0) with respect to our HFR values that did not consider those effects. Further opening of the core shells has also been investigated and did not give rise to significant systematic change on the transition probabilities.